Machine vision-based impurity content assessment of paddy grains for pre-storage quality monitoring - Liu Yang; Xinfeng Hu; Can Shu; Jiaming Wang; Nianwu Wei; Tianqing Liu; Qian Liu; Menghao Zhao; Zhiwei Liu; Shaoyun Song (Journal of Stored Products Research, 2026)

Quantifying tire wear particle dynamics: insights from a hydrological-based material flow analysis in urban watersheds - Lebing Ying; Shujie Xu; Jiaming Wang; Shu-Chien Hsu (Journal of Industrial Ecology, 2026)
Tire wear particles (TWPs) constitute a significant fraction of total microplastic release, necessitating quantification for effective management. While material flow analysis (MFA) quantifies their pathways from generation to environmental sinks, existing approaches apply uniform transfer coefficients across entire regions, obscuring critical spatial heterogeneity essential for assessing ecosystem exposure. This study developed a spatially explicit, process-based MFA framework by integrating mechanistic TWP generation modeling with hydrological rainfall-runoff processes to quantify TWP generation, road surface accumulation, and storm-driven mobilization in Hong Kong. Results indicate an annual per capita TWP generation of 0.28 kg/person/year, notably lower than the global average. Over half of the generated TWPs were mobilized by stormwater runoff after road surface deposition. The hydrological transport pathway to surface water exhibits pronounced spatial and event-driven heterogeneity. Spatially, while suburban districts with extensive road networks dominated absolute emissions (24%), dense urban cores exhibited generation intensities 15 times higher and washoff intensities 18 times greater than outlying low-density areas. In terms of event dynamics, storm-event modeling demonstrates that extreme precipitation following prolonged dry periods can mobilize 30% of annual TWP loads within 24 h, fundamentally reorganizing pollution distributions. This framework provides a transferable tool for pinpointing TWP hotspots and informing targeted mitigation strategies in urban watersheds worldwide.

Cerium-modified Cu-SSZ-13 catalysts: Enhanced low-temperature activity and hydrothermal stability for efficient NOx reduction - Bin Guan; Kaiyou Shu; Lei Zhu; Tiankui Zhu; Zhongqi Zhuang; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Hongtao Dang; Luyang Zhang; et al. (Journal of Environmental Chemical Engineering, 2026)

Impact of Sedimentary Environmental Evolution on Organic Matter Enrichment in Upper Paleozoic Marine-Continental Transitional Shales in the Shenfu Block, Eastern Ordos Basin, China: Evidence from Geochemistry - Yanchao Zhang; Xiangdong Yin; Shu Jiang; Litao Ma; Jiaming Li (Journal of Earth Science, 2026)

Research on emission control performance of SSCR system based on multi-condition operation and three-high tests - Bin Guan; Kaiyou Shu; Lei Zhu; Tiankui Zhu; Zhongqi Zhuang; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Hongtao Dang; Luyang Zhang; et al. (Fuel, 2026)

Modern pollen analysis on peatlands across monsoonal China and its implications for reconstruction - Shu Chen; Mengmeng Wang; Chunmei Ma; Tianyi Tang; Rui Ke; Jiaming Hou; Xinrong Zhang; Zhuo Zheng; Xiayun Xiao; Yan Zhao; Huayu Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

The role of ammonia in the global energy transition: opportunities and challenges in ammonia gas turbine technology - Shuai Chen; Bin Guan; Lei Zhu; Zhongqi Zhuang; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Kaiyou Shu; Hongtao Dang; Luyang Zhang; et al. (Fuel, 2026)

High-efficiency catalytic removal of N2O from ammonia-fueled engine exhaust - Bin Guan; Zhongqi Zhuang; Lei Zhu; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Kaiyou Shu; Hongtao Dang; Luyang Zhang; Tiankui Zhu; et al. (Fuel, 2026)

Flexible CeO₂ surface engineering optimizes atomically dispersed Ru catalyst-support interaction for enhanced ammonia decomposition - Xuehan Hu; Bin Guan; Lei Zhu; Chenyu Zhu; Zhongqi Zhuang; Sikai Zhao; Junyan Chen; Kaiyou Shu; Hongtao Dang; Junjie Gao; Luyang Zhang; Tiankui Zhu; et al. (Chemical Engineering Journal, 2025)

Pd/F-Al2O3 catalyst for N2O-NH3-SCR with ultrahigh low-temperature activity and resistance to inhibitory gases: Property research of being rich in oxygen vacancies with free electrons and reaction mechanisms - Zhongqi Zhuang; Bin Guan; Lei Zhu; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Kaiyou Shu; Hongtao Dang; Junjie Gao; Luyang Zhang; Tiankui Zhu; et al. (Chemical Engineering Journal, 2025)

Enhancing the separation of iron and manganese from high-iron rhodochrosite through medium-low temperature calcination and leaching - Jiaming Chen; Jiancheng Shu; Huimin Yang; Sha Zhang; Jun Luo; Jing Wang; Hongyuan Zhao; Zongchen Wei; Yong Yang; Zongyu Deng; Mengjun Chen (Process Safety and Environmental Protection, 2025)

An artificial intelligence and blockchain technology-based data management framework for multicenter randomized controlled trials - Dongyuan Yun; Xiaohang Wu; Xi Chen; Yahan Yang; Yuanjun Shang; Shaopeng Liu; Dinesh Visva Gunasekeran; Duoru Lin; Lixue Liu; Lanqin Zhao; Wenben Chen; Jingjing Chen; et al. (Science Bulletin, 2025)

Selective complex leaching of Cu, Zn, and Cd from recycled copper smelting fly ash using NH3-NH4Cl system and kinetic analysis - Fan Lin; Tianya Lei; Jiancheng Shu; Mengjun Chen; Jibamu Duo; Xiangfei Zeng; Yunhui Han; Shaoqin Chen; Jiaming Chen; Weiping Huang; Jun Luo (Process Safety and Environmental Protection, 2025)

Enhanced removal of Cr(VI) from aqueous solutions by an electric field and iron–manganese oxalate composites - Shushu Liao; Kaiyuan Liang; Jiancheng Shu; Yunhui Han; Jiaming Chen; Shaoqin Chen; Jun Luo; Shengjie Wang; Mengjun Chen; Hanke Wei; Zongyu Deng (Journal of Environmental Chemical Engineering, 2025)

The involvement of tumor necrosis factor receptor-associated factor 6 in regulating immune response by NF-κB at pre-molt stage of Chinese mitten crab (Eriocheir sinensis) - Jialin Li; Yuhan Ma; Zihao Wu; Jiaming Li; Fengchi Wang; Zhichao Yang; Yuting Xi; Dazuo Yang; Yusheng Jiang; Qilin Yi; Shu Huang (Fish & Shellfish Immunology, 2024)

Assessing geological hazard susceptibility and impacts of climate factors in the eastern Himalayan syntaxis region - Jiaming Yao; Yanbing Wang; Teng Wang; Beibei Zhang; Yuming Wu; Xin Yao; Zheng Zhao; Shu Zhu (Landslides, 2024)

A novel method for efficiently recycling platinum group metals and copper by Co-smelting spent automobile catalysts with waste-printed circuit boards - Rong Huang; Songshan Zhou; Jiaming Chen; Xiangfei Zeng; Yunhui Han; Jinchuan Qin; Yao Huang; Fan Lin; Xi Yu; Shushu Liao; Zhiqiang Chen; Yubin Han; et al. (Journal of Cleaner Production, 2024)

Enhanced recovery of high purity Cu powder from reclaimed copper smelting fly ash by NH3·H2O–NH4Cl slurry electrolysis system - Jiaming Chen; Tianya Lei; Jiancheng Shu; Wenxing Cao; Xiangfei Zeng; Fan Lin; Shushu Liao; Mengjun Chen; Liang Wei; Weiping Huang (Journal of Cleaner Production, 2023)

Statistical modeling and dependence analysis for tide level via multivariate extreme value distribution method - Ali Tian; Xufeng Shu; Jiaming Guo; Haoyun Li; Renchuan Ye; Peng Ren (Ocean Engineering, 2023)

Self-powered health monitoring with ultrafast response and recovery enabled by nanostructured silicon moisture-electric generator - Yuhang Song; Chang Shu; Zheheng Song; Xuelian Zeng; Xianrong Yuan; Yanan Wang; Jiaming Xu; Qianyue Feng; Tao Song; Beibei Shao; Yusheng Wang; Baoquan Sun (Chemical Engineering Journal, 2023)

FOXO-like Gene Is Involved in the Regulation of 20E Pathway through mTOR in Eriocheir sinensis - Jiaming Li; Yuhan Ma; Zhichao Yang; Fengchi Wang; Jialin Li; Yusheng Jiang; Dazuo Yang; Qilin Yi; Shu Huang (Journal of Marine Science and Engineering, 2023)
The Forkhead Box O (FOXO) gene plays a key role in various biological processes, such as growth, metabolism, development, immunity and longevity. Molting is an essential process for crustacean growth, which is mainly regulated by 20-hydroxyecdysone (20E) and molt-inhibiting hormone (MIH). Although the role of FOXO in regulating the immune response of crustaceans is well documented, its involvement in controlling crustacean molting remains unclear. In this study, a FOXO-like gene (designed as EsFOXO-like) was identified in Eriocheir sinensis, and the regulation of the 20E pathway by EsFOXO-like was also investigated. The coding sequence of EsFOXO-like was 852 bp, which consisted of 283 amino acids including a conserved Forkhead (FH) domain. EsFOXO-like shared high similarity with FOXO genes from other crustaceans, and the mRNA expression levels of the EsFOXO-like gene were highest in the hepatopancreas and lowest in the hemocytes. However, transcription and protein expression of the EsFOXO-like gene were found to be up-regulated only during the pre-molt stage in the hepatopancreas, with lower expression levels observed at the post-molt stage. To explore the role of EsFOXO-like in the 20E pathway, EsFOXO-like was firstly inhibited by a specific FOXO inhibitor (AS1842856) and then through an EsFOXO-like dsRNA injection, respectively, and the results showed that the relative expression levels of EsFOXO-like were notably decreased in the hepatopancreas after both the inhibitor and dsRNA treatments. The 20E concentration, the mRNA expression levels of the 20E receptors including the ecdysone receptor (EcR) and the retinoid-X receptor (RXR) and EsmTOR transcription in the AS1842856 group or the EsFOXO-RNAi group were all significantly higher than that in the control group, while the mRNA expression level of EsMIH was significantly decreased after EsFOXO-like inhibition. To further investigate whether the EsFOXO-like acts through mTOR or not, Rapamycin was administered to inhibit mTOR activity in EsFOXO-like inhibited crabs. The results revealed a significant reduction in the concentration of 20E and the expression level of EsMIH in the AS1842856 + Rapamycin group compared to the AS1842856 + DMSO group, accompanied by an increase in EsEcR and EsRXR expression. These findings collectively suggest that EsFOXO-like regulates the 20E pathway through mTOR, which offered valuable insights into the understanding of the molting process in crustaceans.

Effects of leaf scorch on chlorophyll fluorescence characteristics of walnut leaves - ChangJie Xing; ShiWei Wang; CuiFang Zhang; Tong Guo; HongLong Hao; ZhuoYa Zhang; Sheng Wang; JiaMing Shu (Journal of Plant Diseases and Protection, 2023)

Dynamic Analysis of the Rock Burst Potential of a Longwall Panel Intersecting with a Fault - Lishuai Jiang; Peng Kong; Peipeng Zhang; Jiaming Shu; Qingbiao Wang; Lianjun Chen; Quanlin Wu (Rock Mechanics and Rock Engineering, 2020)

Effect of Fracture Heterogeneity on Rock Mass Stability in a Highly Heterogeneous Underground Roadway - Peng Kong; Lishuai Jiang; Jiaming Shu; Atsushi Sainoki; Qingbiao Wang (Rock Mechanics and Rock Engineering, 2019)

Numerical Analysis of Support Designs Based on a Case Study of a Longwall Entry - Lishuai Jiang; Peng Kong; Jiaming Shu; Kegong Fan (Rock Mechanics and Rock Engineering, 2019)